Depolarization effect of a vapor cell in atom-based radio-frequency electric field measurement. (8th August 2018) - Zhang, Wanfeng; Song, Zhenfei; Mu, Huihui; Bao, Shanxia
Abstract: The Rydberg atom can be used as an active probe for precision radio-frequency (RF) electric field (E-field) measurement; however, the RF cavity resonance and scattering effect of an atomic vapor cell lead to polarization distortion inside the cell, and the depolarization effect limits the sensitivity and accuracy of E-field measurement. The finite element simulation and characteristic mode analysis of a hollow-cavity model are implemented to find an optimized solution of minimizing such depolarization. Manipulating atoms in the middle layer of a vapor cell along an incident field vector can avoid the depolarization, which is validated by the vector distribution measurement at 15.09 GHz.